An evaluation of the transmission of the policy interest rate to the financial system’s interest rates in Colombia (2016)
This paper studies monetary policy transmission using several statistical tools -- We find that the relationships between the policy interest rate and the financial system’s interest rates are positive and statistically significant, and transmission is complete eight months after policy shocks occur -- The speed of transmission varies according to the type of interest rates -- Transmission is faster for interest rates on loans provided to households, and is particularly rapid and complete for rates on preferential commercial loans -- Transmission is slower for credit card and mortgage rates, due to regulatory issues (interest rate ceilings)